Electronic access to mouse tumor data: the Mouse Tumor Biology Database (MTB) project. - Bult, C J (1999)
The Mouse Tumor Biology (MTB) Database supports the use of the mouse as a model system of hereditary and induced cancers by providing electronic access to: (i) tumor names and classifications, (ii) tumor incidence and latency data in different strains of mice, (iii) tumor pathology reports and images, (iv) information on genetic factors associated with tumors and tumor development, and (v) references (published and unpublished data). This resource has been designed to aid researchers in such areas as choosing experimental models, reviewing patterns of mutations in specific cancers, and identifying genes that are commonly mutated across a spectrum of cancers. MTB also provides hypertext links to related on-line resources and databases. MTB is accessible via the World Wide Web at http://tumor.informatics.jax.org. User support is available for MTB by Email at mgi-help@informatics.jax.org